NGOs, Controversies, and "Opening Up" of Regulatory Governance of Science in India. (December 2017) - Pandey, Poonam; Sharma, Aviram
Nongovernmental organizations (NGOs) and scientific controversies are often the common denominators in most of the cases that have significantly shaped science and society relationships in the Global South during the past two decades. National and international NGOs and their network have often facilitated the "opening up" of regulatory governance in multiple sectors. This article draws from three cases—the bottled water controversy, the agribiotechnology debates, and the nanotechnology initiatives—and charts out the role of the NGOs and controversies in (re)defining the science-society relationship in India. The three cases illustrate how NGOs and controversies by their presence or absence at various stages of technology development shape the regulation-making exercise and the overall regulatory governance of science and technology.